Analysis Of Pharmaceutical Services In Outpatient Services Of Pharmaceutical Installation At Baubau City Hospital - Akmal amrin; Hamzah, Hasty; Harisma Damayanti, Restu (International Journal of Multidisciplinary Learners, 2025)
Pharmaceutical services in the outpatient pharmacy installation of the hospital involve direct and responsible care related to pharmaceutical products, aimed at improving patient quality of life. This study aims to evaluate the pharmaceutical services at the Outpatient Pharmacy Installation of RSUD Kota Baubau. The research uses a descriptive qualitative method with a questionnaire. The study population consists of all pharmacists at the Outpatient Pharmacy Installation of RSUD Kota Baubau, with the sample including 2 respondents: the Head of the Pharmacy Installation and a pharmacist at the Outpatient Pharmacy Installation of RSUD Kota Baubau. The results indicate that, overall, the standards of Pharmaceutical Services (PK) at the Outpatient Pharmacy Installation of RSUD Kota Baubau comply with the standards set out in the Ministry of Health Regulation No. 72 of 2016, with the following percentage values: PK 1 Standard Operating Procedure (SOP) for Pharmacy Management at 100%, PK 2 Standard Operating Procedure (SOP) for Clinical Pharmacy Services at 90.90%, PK 3 Drug Information Services at 83.3%, PK 4 Evaluation at 100%, PK 5 Prescription at 100%, PK 6 Visit at 100%, PK 7 Medication Therapy Monitoring (MTM) at 100%, PK 8 Drug Utilization Evaluation (DUE) at 100%, and PK 9 Adverse Drug Reaction Monitoring (ADR) at 100%. The total percentage of compliance with the pharmaceutical service standards in the outpatient service is 97.13%.